Answer:
A' = (-1,3) - A = (3,11)
B' = (-2,2) - B = (2,2)
C' = (-2,1) - C = (1,2)
D' = (-1,1) - D = (1,1,)
Explanation:
We have the polygon ABCD transformed to the polygon A'B'C'D' with the co-ordinates,
A' = (-1,3), B' = (-2,2), C' = (-2,1) and D' = (-1,1).
Since, the polygon is rotated 90 counterclockwise about the origin.
The co-ordinates (x,y) of ABCD will change to (-y,x) for A'B'C'D'.
So, we will change the co-ordinates (-y,x) of A'B'C'D' to (x,y) which gives the co-ordinates of ABCD.
That is,
Take the y-value to the 1st position and x-value to the second multiplied by negative sign.
Thus, we have,
A' = (-1,3) ------------------ A = (3,1)
B' = (-2,2) ------------------ B = (2,2)
C' = (-2,1) ------------------ C = (1,2)
D' = (-1,1) ------------------- D = (1,1,)